Timing carbon turnover (delta C-13) in weaned piglet's brain by IRMS - Saleh, Mayra A. D. [UNESP]; Dos Santos, Luan S. [UNESP]; Berto, Dirlei A. [UNESP]; Amorim, Alessandro B.; Costa, Vladimir E. [UNESP]; Ducatti, Carlos [UNESP] (Acad Brasileira De Ciencias, 2018)
Isotope-ratio mass spectrometry (IRMS) is a potential tool that provides time-integrated estimate of assimilated and not just ingested nutrients. This feature turned possible its application to evaluate the effects of dietary nucleotides and glutamate on carbon turnover (delta C-13) in the brain of weanling piglets. Eighty-seven piglets weaned at 21-day-old were used, being three piglets slaughtered at day-0 (prior to diet-switch) and, the remaining 84 randomly assigned in a complete block design with a 2 x 2 factorial arrangement of treatments (two nucleotide levels: 0% and 0.1% and, two glutamate levels: 0% and 1%). On trial days 3, 6, 9, 14, 21, 35 and 49, three piglets per treatment were also slaughtered. The samples were analyzed by IRMS and adjusted to the first-order equation by a nonlinear regression analysis using NLIN procedure of SAS, in order to obtain the exponential graphics. The carbon turnover (t(95%)) verified for cerebral tissue was faster (P<0.05) for diet containing glutamate in comparison to other diets, supporting the fact that glutamate contributed to develop the piglets' brain, due to the fastest incorporation of C-13-atoms in this tissue at post-weaning phase, despite the energy deficit experienced by them.
Keywords: additives; amino acids; isotopic dilution; stable isotopes; swine